Bahasa yang membeku: Foregrounding dan kritik sosial dalam puisi ‘2000 Taht Al-Sifr’ karya Nizar Qabbani - Toppo, Ananda Atasya; Ramadhan, Ilham; Agussalim, Andi (Universitas Mulawarman, 2025)
This study aims to analyze the linguistic structure in the poem 2000 Taht al-Sifr by Nizar Qabbani using the foregrounding theory approach. The main focus of this study is on the techniques of repetition and linguistic deviation used by the poet to create aesthetic effects and convey ideological meaning. The research employs a qualitative descriptive method with a textual analysis approach. Data were collected through literature study and close reading of the poem, then analyzed based on grammatical deviations and recurring linguistic patterns. The results show that the static repetition found in the poem creates a sense of stagnation and emotional impasse, while linguistic deviations, including extreme metaphors and unconventional syntax, generate symbolic tension that reflects social alienation and political crisis after the defeat of the Arab world in 1967. Foregrounding in this poem not only enhances the poetic expression but also functions as a form of critique of the socio-political condition. These findings indicate that linguistic elements in poetry play a crucial role in constructing meanings that go beyond aesthetic expression.